Data for article: Microplastics in Arctic Waters of the Finnish Sámi Area - Soininen, Tuomo; Uurasjärvi, Emilia; Koistinen, Arto; Mustonen, Tero; Hämäläinen, Lauri; Huusari, Noora; Feodoroff, Juha; Moshnikoff, Jouko; Feodoroff, Pauliina (Zenodo, 2023)
Description of the dataset: This dataset was created in 2021 and made open in 2023 Lapland_Sampling.xlsx contains all sampling dates and coordinates alongside with sample names, volumes, area descriptions and codes used to describe the sites in the article. Lapland_RawData.xlsx contains all the raw data for all the samples.This includes polymer types, particle sizes and an estimation ofparticle mass. Furthermore, the file contains a table with all the polymer types and their counts from allsamples. Data creation and processing: The raw data was created by measuring filtered water samples with FPA-FTIR . The spectral analysis was done with siMPle (Primpke et al. 2020, Applied Spectroscopy , 74, 1127-1138, https://doi.org/10.1177/0003702820917760 ).